Balls! : round 2 - Rosen, Michael J., 1954-; Margeson, John, 1961- (Plain City, OH : Darby Creek Pub., 2008)
Learn about the balls used in baseball, softball, bowling, bocce ball, croquet, billiards, the shot put and other "oddballs": how they're made, why they look the way they do, some amazing facts about their history ... and a bit about the games that use them, too.
A Junior Library Guild selection
Ages 10 and up.
Includes bibliographical references (p. 76-78) and index.
8 13 23 29
Keywords: Balls (Sporting goods) -- Juvenile literature; Ball games -- Juvenile literature; Balls (Sporting goods); Ball games